Human Resource Management across Generations within the Context of World of Work 4.0 - Renta Skýpalová; Hana Stojanová; Hermann Troger; Zdeněk Caha (Ital Publication, 2023)
The aim of the paper is to evaluate the expectations of cohorts of workers from Generations X, Y, and Z with regards to their perceptions of what a